Na začetku in koncu demokracije je (bila) beseda - Verčič, Dejan (Teorija in praksa, 2022)
Aristotle wrote Rhetoric next to Politics intending to help the Athenian democracy against demagogy. Similarly, 2,000 years later, Harold Lasswell alongside political science answering the questions “Who Gets What, When, and How”, instituted communication science to answer the questions “Who Says What, in What Channel, to Whom, with What Effect”, in another defence of democracy against demagogy. We face a similar challenge today. The pluralisation of media production and personalisation of media consumption are threatening the sustainability of the community named polis, the political community in and about which we can communicate because it is common to us and which we share (lat. communis ›?communicatio)
Keywords: Demokracija; komunikologija; Politične vede; Politično komuniciranje; politologija